Job Stress and Burnout Syndrome in a Sample of Rural Health Workers, Behvarzes, in Tehran, Iran - Maryam Salehi (Iranian Journal of Psychiatry, 2011)
"nObjective:  In the last 30 years, ever since the PHC network in Iran has been established, the job duties of Behvarzes (Mental Health Workers in rural areas) have been constantly increasing. The aim of this study was to determine the burnout level, mental health status and the severity of occupational stress among Behvarzes. "nMethods: All Behvarzes (227) working in areas covered by Iran University of Medical Sciences were considered for participation in the study. Maslach Burnout Inventory, GHQ-12, and Stainmentz questionnaires were used. "nResults: The completed questionnaires were returned by 93% of the subjects. The mean score of job stress was in the first percentile (42.8 ± 27.16). 17.6% of the study subjects had moderate to severe level of burnout; 12.3%, 5.3% and 43% of the subjects had abnormal scores on emotional exhaustion, depersonalization and personal subscales respectively; and 28.3% of the cases were suspected to have mental disorders by GHQ. "nDiscussion: In spite of increasing assigned jobs to Behvarzes, job stress and burnout are not seriously distressful. Providing more desirable personal accomplishment for Behvarzes by reducing job ambiguity/ conflict, participating in planning new programs, and improving interaction with health authorities may help them to overcome their job related pressure and increasing workload.